Identification and Epigenetic Analysis of a Maternally Imprinted Gene Qpct - Guo, Jing (Mol Cells, 2015)
Most imprinted genes are concerned with embryonic development, especially placental development. Here, we identified a placenta-specific imprinted gene Qpct. Our results show that Qpct is widely expressed during early embryonic development and can be detected in the telecephalon, midbrain, and rhombencephalon at E9.5–E11.5. Moreover, Qpct is strikingly expressed in the brain, lung and liver in E15.5. Expression signals for Qpct achieved a peak at E15.5 during placental development and were only detected in the labyrinth layer in E15.5 placenta. ChIP assay results suggest that the modification of histone H3K4me3 can result in maternal activating of Qpct.